The proportion of postpartum depression and its association with mode of delivery and parity - Novy Ratnasari Sinulingga; Amel Yanis; Fika Tri Anggraini (Institute of Computer Science (IOCS), 2023)
Postpartum depression is a severe mood problem that can harm postpartum women. Depression is three times more common in the postpartum period than at any other time in a woman's life. The prevalence of postpartum depression in the world ranges from 17.22% and 11.76% in Indonesia. Depression at the age of ≥15 years in West Sumatra (8.2%) and Padang (7.8%). Many factors can contribute to postpartum depression. This study aimed to determine the proportion of postpartum depression and its association with the mode of delivery and parity. This study was an Analytical survey with a Cross-sectional design at the Andalas Health Center from July to August 2022. The study population was all postpartum mothers (3-6 months), and the study sample was 134 with Proportional random sampling from each ward. Data had collected through interviews and assessment of postpartum depression using the Edinburgh Postnatal Depression Scale questionnaire by respondents. Data analysis used univariate and bivariate (Chi-square). The results describe that the proportion of postpartum depression at the Andalas Health Center was 36.6%. The results reported that the mode of delivery had no significant association with postpartum depression (p=0.812). Parity showed a statistically significant association with postpartum depression (p=0.016).